Energy efficient resource sharing using a traffic‐oriented routing scheme for cognitive radio networks. Issue 1 (1st March 2014) - Mavromoustakis, Constandinos X.; Mastorakis, George; Bourdena, Athina; Pallis, Evangelos
Abstract : This study proposes a resource intensive traffic‐aware scheme, incorporated into an energy‐efficient routing protocol that enables maximum energy conservation and efficient data flow coordination, among secondary communicating nodes with heterogeneous spectrum availability in cognitive radio networks. The proposed scheme associates the backward difference of the traffic moments of each node according to a Fibonacci model, with the sleep‐time duration, in order to tune the activity periods for achieving optimal energy conservation. Efficient routing protocol operation, as a matter of maximum‐possible routing paths establishments and minimum delays is obtained, by utilising a signalling mechanism, developed based on a simulation scenario that includes secondary communication nodes, operating over television white spaces. The validity of the proposed Fibonacci‐based backward traffic difference is verified, by conducting experimental simulation tests. Simulation results validate the efficiency of the proposed traffic‐aware scheme for minimising energy consumption and routing delays, as well as maximising resources exchange between secondary communication nodes.